Study on Change Characteristics of Non Effective Precipitation Days in Southwest China from 1960to 2016 - LIU Minghan; QIN Nianxiu; CHEN Yanlian; HUANG Jiali (Renmin Zhujiang)
Based on the daily precipitation data of 117 stations in southwest five provinces(Guangxi, Yunnan, Guizhou, Sichuan and Chongqing) from 1960 to 2016 (57 a), this paper establishesthe time series (LCDD) of annual and seasonal non effective precipitation days by the noneffective precipitation days index, and analyzes the temporal and spatial change rules of noneffective precipitation days by the methods of Mann Kendall trend analysis and inverse distanceweight. The results show that the number of days without effective precipitation and the number ofdroughts in Southwest China have a trend of fluctuating growth. The number of days withouteffective precipitation is mainly in summer and autumn, while the occurrence of drought is mainlyin spring and winter. In spring and winter, Yunnan and Sichuan are in serious drought, while insummer and autumn, Guangxi, Guizhou and Chongqing are in serious drought. Yunnan and southwestSichuan are the areas with the maximum number of days without effective precipitation. The annualchange of the longest consecutive days without effective precipitation in Southwest China shows aslow upward trend, with accelerating rise since 2010.